Fonte de infecção e genotipagem de Toxoplasma gondii durante o surto de toxoplasmose em Santa Maria, Brasil - Minuzzi, Camila Encarnação (2020)
Toxoplasma gondii is highly widespread worldwide, due to its high adaptability and different forms of transmission. This parasite has a wide range of species as intermediate hosts , in which occurs the formation of tissue cysts . The definitive hosts are the felids, which excrete oocysts in their feces. Oocysts are an important source of infection in humans. They can be ingested in contaminated food or water. Toxoplasmosis in humans has different clinical presentations, but it gains more relevance when infection outcomes during pregnancy: congenital toxoplasmosis. In 2018 there was an outbreak of toxoplasmosis in humans in the municipality of Santa Maria, southern Brazil, which was considered the largest outbreak of Toxoplasmosis ever described in the world. This thesis was developed in order to collaborate in the elucidation of this great outbreak. Chapter 1 contains a study that presents the molecular characterization of T. gondii from placentas of patients with acute toxoplasmosis during the outbreak. In this study, bioassies were performed on mice and genotyping of the isolates . With this, it can be verified that it was an atypical genotype that had never been described before. In the study presented in chapter 2, the outbreak source of infection was investigated. For this, bioassaies were carried out with pigs that received water from different sources in the city. The animals' serology was periodically performed, and it was noticed that seroconversion occurred. Subsequently, a second bioassay using mice that were inoculated with tissues from these pigs, demonstrated that there was active infection of T. gondii in the tissues, thus suggesting that water was a potential source of infection in this outbreak.